Prospects and challenges of targeted extracellular vesicles drug delivery for cancer treatment - Fatemeh Maher; Ali Samadi; Peyman Asadi; Isabella Jodoin (Extracellular Vesicle)
Extracellular vesicles (EVs) have the ability to alter the phenotypes and functions of other cells as well as reflect the state of the cell from whence they originated.Extracellular vesicles, or EVs, are membrane-bound nanostructures released into the extracellular environment. Under both normal and pathological circumstances, they are widely discharged from cells and display a variety of sizes, contents, and surface marks. These EVs are abundant in human serum, yet it might be difficult to separate them from non-EV lipid particles and serum proteins. These vesicles influence several physiological and pathological processes, including those that occur in the tumor microenvironment (TME), by transporting different cellular constituents such as proteins, mRNAs, miRNAs, DNA, and lipids across distances. EVs are potential possibilities for therapeutic agents, medication delivery methods, and disease biomarkers due to their crucial functions in cellular communication. EV detection has the potential to serve as a diagnostic biomarker and can facilitate early identification, particularly in the context of cancer diagnosis. Furthermore, EV subtypes may be clinically significant as different subtypes are emerging as targeted medication delivery methods. There is still a need for non-invasive biomarkers to track biological processes for treatment and diagnosis. In the future, utilizing EVs' distinct composition may open up new possibilities for enhanced diagnosis and treatment.